تمارين


 

1

 

      ►         

 

8 – 3 , ( -4) : 2 + 4

(6-)-20 : (3+7 ) , 2

 

 

              ►         

 

(-6) – (+9) + (+10) – (+1)

    

 

 

                                     13 + 2.( - 8 – 6 )

    

2

 

 

10 + 8 + 4 + 9 + 2 =

1 – 8 – 1 =

5 + 2 + 10 + 10 + 4 =

5 + 6 x 3 + 5 =

6 + 3 –8 x (–9) =

5 ÷ 5 + 5 + 2 =

9 + 9 + 16 ÷ 4 =

7 x 7 – 9 ÷ 1 + 9 =

1 + 1(7 + 2) =

9 + 2(10 – 5) =

9 + 9 ÷ (1 + 8) =

5 + 2 ÷ (9 – 8) =

2 + 8[1 + 7(9 + 1) + 4] =

9 + 3[9 + 4(2 – 4) + 7] =

1 + 10[1 + 6 ÷ (5 + 1) + 5] =

18 + 20[8 – 13 ÷ (12 + 1) + 2] =

5 + 6{7 + 1[7 + 8(2 + 2) + 1] + 8} =

2 – 1{8 + 3[8 + 2(10 + 9) + 1] + 1} =

1 – 9{2 – 8[2 + 8 ÷ (1 + 1) + 4] + 2} =

 

               تصحيح  ►                    


www.hassan.ab.ma

Welcome To My Website
hassan.ab.ma © 2017.Free Web Site